Características mineralógicas e granulométricas das fontes de poeiras no Polo Cerâmico de Santa Gertrudes - SP - Oliveira, M.; Zanardo, A.; Carvalho, S. G. De; Rocha, R. R. Da (Associação Brasileira de Cerâmica, 2016)
Abstract Recent studies on the presence of dust flows into the atmosphere show that they can be up to eight times higher than the previously consolidated estimates. With origin mainly attributed to the new demands of uses of soils, fuels and rocks, this concentration can globally modify the main components of the Climate geosystem, and endanger the ecosystem limits which support life on the planet. Despite the importance of Brazil as a producer of mineral and agricultural commodities, and therefore a major producer of mineral dust, few such studies have been conducted. This study is related with this issue in a region known as Ceramic Cluster of Santa Gertrudes that have the largest ceramics industries of Brazil and also large agricultural production. X-ray diffraction and laser diffraction techniques were used to characterize the mineralogical composition and particle size distribution of soil (pedological source), clay mineral (lithological source) and their transformation products (terrigenous and industrial source), considered as the main emission sources of dust in this region. The presence of an assembly of silicate minerals rich in aluminum and iron that prevails in these sources of dust explains the high SiO2, Al2O3 and Fe2O3 contents found in the ore, soil and the atmosphere of the region. The predominance of minerals such as kaolinite clays can be considered as pedological source diagnostic, while the predominant illitic clays characterize the lithology source. The granulometric studies revealed that, among the various sources, the pedological is the one with the highest fraction of clay materials in MP10, and therefore has the higher potential to contribute with the resuspension processes that are efficient to transfer mineral dusts of surface to the atmosphere.

Resumo Estudos recentes relativos à presença de fluxos de poeiras que entram na atmosfera atestam que eles podem ser até oito vezes maiores do que as estimativas até então consolidadas. Com origem atribuída principalmente às novas demandas de usos dos solos, combustíveis e rochas, essa concentração pode modificar globalmente os principais componentes do Geossistema Climático e colocar em risco os limites ecossistêmicos que suportam a vida no planeta. Em que pese a relevância do Brasil como produtor de commodities minerais e agrícolas e, portanto, um grande produtor de poeiras minerais, poucos estudos dessa natureza têm sido realizados. O presente estudo aborda esse tema em uma região conhecida como Polo Cerâmico de Santa Gertrudes que, além de abrigar as maiores indústrias cerâmicas do Brasil, destaca-se pela sua grande produção agrícola. Técnicas de difração de raios X e difração a laser foram utilizadas para caracterizar a composição mineralógica e granulométrica relativamente dos solos (fonte pedológica), minério de argila (fonte litológica) e seus produtos de transformação (fonte terrígena e industrial), considerados como principais fontes emissoras de poeiras dessa região. A presença de uma assembleia de minerais silicatados ricos em alumínio e ferro que predominam nessas fontes de poeiras explica os altos teores de SiO2, Al2O3 e Fe2O3 encontrados no minério, solos e na atmosfera da região. O predomínio de argilas cauliníticas pode ser considerado como diagnóstico de fonte pedológica, enquanto que o predomínio de argilas ilíticas caracteriza a fonte litológica. Os estudos granulométricos revelaram que, entre as diferentes fontes, a pedológica é a que possui maior volume de materiais argilosos na fração MP10 e, portanto, a que mais tem condição de contribuir com os processos de ressuspensão que são eficientes na transferência de poeiras minerais da superfície para a atmosfera.
Mineralogical and granulometric characteristics of dust sources in the Ceramic Cluster of Santa Gertrudes - SP
Keywords: air quality; particulate matter; geosystem Climate; ceramics industries; qualidade do ar; material particulado; Geossistema Climático; indústrias cerâmicas